PERLINDUNGAN HAK HAK ANAK DALAM SISTEM PERADILAN PIDANA KENAKALAN PADA REMAJA PERSPEKTIF HUKUM ACARA PIDANA (study kasus DP3AP2 DIY - Lisa Rustandi; Siti Masitoh (Bajang Institute, 2024)
Formation and development are based on the principles of non-discrimination, the best interests of the child, life, life development and continuity, respect for the child's views and good management. Motivation for the creation of schools that are safe and enjoyable for students because they are free from violence between students and violence committed by educators and education staff. Children's rights are rights that must be recognized and protected by the State referring to the principles of justice including the right to be heard, the right to be respected, the right to be protected. In cases involving children, both perpetrators and victims must have their rights protected based on existing regulations. In Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, it is explained in Article 1 Paragraph 2 that Child Protection is all activities to guarantee and protect children and their rights so that they can live, grow, develop and participate optimally in accordance with human dignity and protection and protection from violence and discrimination